Człowiek w myśli Jana Pawła II - Nagy, Stanisław (Horyzonty Wychowania, 2017)
The aim of this article is presenting the understanding of theconcept of „human being”. The author makes „John Paul II’sthought” the source of his reflection. The question: „who is man?”becomes the starting point of the deliberations.Firstly, he presents man as the subject dominating the worldof objects. This term denotes man having the ability to learn thetruth about the world in a special and specific way and, as a consequence,to learn the truth about himself (self-cognition). It alsodenotes man who is a separate being, having his own, distinctand unique personality.Secondly, he draws attention to man as a person and theresulting characteristics: his rationality, freedom, morality andconsciousness.And thirdly, the author (following John Paul II) calls mana Christian. He claims that it is this „specification” of man asa person that determines his perspective, not only natural, butfirst of all supernatural. The key to such vision of man is JesusChrist – the Redeemer, who as an example of man’s image byvirtue of God’s nature being realised in Him and at the same timefull human nature, fully reveals man to man himself and showshim his highest vocation. Man’s image understood and interpretedin this way leads to the necessity to discern dignity, greatnessand full humanity he deserves by virtue of Redemption.